A novel approach for engineering DHCM/GelMA microgels: application in hepatocellular carcinoma cell encapsulation and chemoresistance research - Zhou, Dandan; Li, Xiaoxiao; Liu, Wencun; Zhang, Mingjun; Cheng, Ying; Xu, Zhousong; Gao, Jian; Wang, Yiyang (Frontiers in Bioengineering and Biotechnology, 2025)
Liver cancer, a highly aggressive malignancy, continues to present significant challenges in therapeutic management due to its pronounced chemoresistance. This resistance, which undermines the efficacy of conventional chemotherapy and targeted therapies, is driven by multifaceted mechanisms, with increasing emphasis placed on the protective role of the tumor microenvironment (TME). The hepatocellular carcinoma extracellular matrix (ECM), a primary non-cellular component of the TME, has emerged as a critical regulator in cancer progression and drug resistance, particularly in hepatocellular carcinoma cell (HCC). In this study, a hybrid biomimetic hydrogel was engineered by integrating decellularized hepatocellular carcinoma matrix (DHCM) with gelatin methacrylate (GelMA) precursors. This composite DHCM/GelMA hydrogel was designed to replicate the physicochemical and functional properties of the hepatocellular carcinoma ECM, thereby offering a biomimetic platform to explore the interactions between HCCs and their microenvironment. Leveraging a custom-designed microfluidic 3D printing platform, we achieved high-throughput fabrication of HCC-encapsulated DHCM/GelMA microgels, characterized by enhanced uniformity, biocompatibility, and scalability. These microgels facilitated the construction of hepatocellular carcinoma microtissues, which were subsequently employed for chemoresistance studies. Our findings revealed that DHCM/GelMA microgels closely mimic the hepatocellular carcinoma tumor microenvironment, effectively recapitulating key features of ECM-mediated drug resistance. Mechanistic studies further demonstrated that DHCM significantly upregulates the expression of Aquaporin 3 (AQP3) in the encapsulated HCCs. This upregulation potentially activates mTOR signaling-associated autophagy pathways, thereby enhancing chemoresistance in HCCs. These biomimetic models provide a robust and versatile platform for studying the underlying mechanisms of drug resistance and evaluating therapeutic interventions. This innovative approach highlights the potential of DHCM/GelMA microgels as a transformative tool in cancer-associated tissue engineering and anticancer drug screening. By enabling detailed investigations into the role of ECM in chemoresistance, this study contributes to advancing therapeutic research and offers promising strategies to overcome drug resistance, ultimately improving clinical outcomes in liver cancer treatment.